Communities of Practice: New modes of collaboration and networked learning? - Tremblay, Diane-Gabrielle (Proceedings of the International Conference on Networked Learning, 2018)
Over the last decades, there has been more and more interest in various modes of networked learning, knowledge creation, communities or practice (CoPs) but there is not yet a clear identification of the conditions to succeed in such initiatives. This interest for CoPs stems from the fact that organizations expect substantial gains from knowledge development and networked learning. Communities of practice are seen in many organizations as a source of networked learning, and ultimately of competitiveness and innovation. The interest for communities of practice arises from this objective of learning and innovation, but it is viewed as a specific form of learning and sharing, in principle more centred on the individuals and their exchanges than on “management” by the firm, although the firm does seem to have a role to play in fostering such initiatives. Thus, the use of communities of practice has emerged as a way to develop collective skills and organizational learning, in order to foster innovation and success for organizations. In this paper, we identify the conditions of success or failure of communities of practice as a mode of networked learning, knowledge management and knowledge sharing, as these conditions have not yet been established. We first define this new form of learning and knowledge sharing through communities of practice. We then present some of the results concerning success, or more precisely attainment of objectives, as success can be defined in various ways. We do this on the basis of 7 case studies of communities of practice implemented in firms. The empirical results are based on a questionnaire survey administered to the participants of these communities of practice, but also on qualitative interviews and regular work and exchanges with some of the animators and participants in these communities of practice. We highlight some interesting differences observed according to age and gender, as well as some limits and challenges that were observed in the learning and sharing process, which are often underestimated. We mainly highlight the factors which explain success, defined as attainment of objectives, and these are : commitment and motivation of participants for the attainment of objectives, as well as the presence of a leader, animator or steward.